Development of Quality of Life Theory and Its Instruments : The Selected Works of Alex. C. Michalos - Michalos, Alex C. (Springer International Publishing : Imprint: Springer, 2017)
The focus of this volume is on the further development of the Quality of Life Theory and the means to measure the concept. The volume summarizes Michalos' fundamental assumptions about the nature of quality of life or human well-being and explains in detail the two variable theory of the quality of life. It gives an update of the journal Social Indicators Research after forty years, an explanation of the role of community indicators in connecting communities, and a critical review of the much publicized Stiglitz, Sen and Fitoussi report. It deals with the multiple discrepancies theory (MDT), the empirical theory designed to provide the foundation of the pragmatic theory of value. Other concepts discussed in this volume are the stability, sensitivity, and other different features of measures of domain and life satisfaction and happiness, measures of arts-related activities and beliefs, measures of knowledge, attitudes and behaviour concerning sustainable development, and the role of quality of life in sustainable development research. The volume concludes with discussions on connections between social indicators and communities, aspects of community quality of life in Prince George, British Columbia and Jasper, Alberta, and British Columbians' expectations and attitudes going into the third millennium.